Health Awareness And Youth Empowerment Program In The Digital Era - Fitriyanti; Harahap, Huntari; Humaryanto, Humaryanto; Amalya Nasution, Riska; Nofrianda, Rion; Dwi Puspita, Puspa; Eka Putra, Nofrans; Maharini, Indri; Kalsum, Ummi; Aswin, Budi (LPPM Universitas Jambi, 2025)
Background: The fast-paced digital era presents unique challenges to youth health, including gadget addiction, a lack of clean and healthy living behaviors (PHBS), and the risk of bullying. This community service aimed to enhance health awareness and empower children of Indonesian migrant workers (PMI), parents, and teachers at the PPWNI Klang, Selangor, Malaysia, to foster a healthy and smart generation in the digital age. Method: The research employed a community-based approach, involving initial coordination with the partner and using interactive lectures and direct practice for the training. The core activities included psychoeducation sessions on mitigating gadget addiction, PHBS, and bullying, alongside basic health checks. Evaluation and monitoring were conducted using pre- and post-training questionnaires and behavioral observation. The target participants included PMI children, parents, and teachers. Result: From 48 participants attended the basic health checks, which revealed an average cholesterol level of 205.85, a blood glucose average of 107.23, and a uric acid average of 7.05. The findings indicate a prevalence of hypercholesterolemia among the participants. Conclusion: The program is relevant to the research objectives and is expected to reduce bullying rates, increase PHBS awareness, and promote more controlled use of gadgets. This collaboration with PPWNI Klang demonstrates a commitment to forging a healthy, strong, and smart younger generation capable of navigating the digital era.